Modelling a fifth-generation bidirectional low temperature district heating and cooling (5GDHC) network for nearly Zero Energy District (nZED). (November 2021) - Bilardo, Matteo; Sandrone, Federico; Zanzottera, Guido; Fabrizio, Enrico
Abstract: Current sustainability challenges place entire communities at the centre of the energy revolution, rather than individual buildings. The need to develop energy-efficient and low-carbon economies lies at the heart of fifth-generation district heating and cooling (5GDHC) networks. The potential of these networks is represented by a lower working temperature close to the ground temperature, usually between 10 and 25 °C. Thanks to this feature, the network presents optimal conditions to be used as a heat source for reversible heat pumps. 5GDHC networks provide users with a fundamental active role, giving the possibility of extracting and releasing energy into the thermal network, while producing heating and cooling simultaneously. The integration of renewable sources and reduced heat losses are added values to be taken into consideration. Given the limited application of 5GDHC networks, this paper aims to evaluate the energy advantages of coupling several users within a bidirectional fifth-generation network based on the integration of reversible heat pumps with on-site production by renewable sources and waste energy recovery. An integrated model of 5GDHC network with buildings was developed in order to meet the energy needs of a neighbourhood made up of users with different energy profiles throughout a whole year. To enhance future applications, the energy performance of the 5GDHC network model was studied through a simulation tool. An hourly numerical calculation tool was developed to simulate the behaviour of the network and the users' response over an annual period, estimating the energy shared between users during both the heating and cooling seasons. The results obtained are presented not only in terms of energy exchanged in the network, but also in the form of performance indexes of the individual users, identifying advantageous combinations between the users for future design developments of these systems. The outcomes of this paper highlight the integration of established technologies into fifth-generation thermal networks, with a view to a future development of nearly Zero Energy Districts (nZED). Graphical abstract: Highlights: Numerical modelling of a fifth-generation district heating and cooling network. Bidirectional decentralized water source heat pump connected in a thermal network. Dynamic energy assessment tool with global performance indicator.